Comparison of Leavening Ability of Kluyveromyces lactis in Different Bread Dough Formulations - Bekir Gökçen Mazı (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to evaluate the dough proofing activity of Kluyveromyces lactis (ATCC 8585) in different dough formulations and to compare it with the commercial active dry bakery yeast Saccharomyces cerevisiae. Leaving ability of yeasts was tested in lean and rich dough. For both cultures, lean and rich dough mixtures containing 0.3 g of yeast biomass (on dry weight basis) and wheat flour in 15 ml of water was prepared. Rich dough contained also either 2.0 g of sucrose, 2.0 g of lactose or 2.5 g of whey powder. Dough mixtures were incubated at 29°C and volume increase was recorded every 15 min. We determined that Kluyveromyces lactis had higher volume and leavening rates compared to commercial bakery yeast strain in lactose-rich or whey-rich dough. These results demonstrated the potential of Kluyveromyces lactis yeast strain as a suitable culture for whey fortified bread making.